Outcomes of croup in children: COVID‐19 versus non‐COVID‐19 cases - Donna R. Mendez; Gregory Rumph; Joan Richardson; Krishna K. Paul; Dietrich Jehle (Journal of the American College of Emergency Physicians Open)
Abstract Objectives: The emergence of COVID‐19 has revealed its association with croup. The objective of this study was to compare outcomes of COVID‐19 related croup to non‐COVID‐19 related croup during the COVID‐19 pandemic. Methods: This retrospective propensity matched study used data from 2020–2023 in the United States Cohort of the TriNetX database that includes 56 major health care organizations. The analysis compared the outcomes of 2 cohorts of patients between 2 months and 7 years of age: Cohort A had croup and a positive test for COVID‐19 and Cohort B had croup without a positive COVID‐19 test, both within 1 week before or after presentation with croup. Outcomes were death, admission to the hospital, intensive care unit (ICU) admission, respiratory rate >60, and oxygen saturation <90 within 7 days after the diagnosis of croup. Results: There were 2590 patients with COVID‐19 related croup and 103,439 patients with non‐COVID‐19 croup. The final propensity matched cohort included 5180 patients evenly divided between groups. When both groups were compared based on outcomes after matching, there was twice the risk of the patient being admitted to the hospital with COVID‐19 croup (risk ratio [RR] = 2.12; 95% confidence interval [CI] 1.59–2.84; P < 0.001). Those with COVID‐19 related croup had significantly increased risk of being admitted to the ICU (RR = 4.90; 95% CI 3.11–7.73; P < 0.001). The patients with COVID‐19 related croup were more likely to have a respiratory rate ≥60 (RR = 2.00; 95% CI 1.18–3.37; P = 0.008) and oxygen saturation ≤90% (RR = 2.12; 95% CI 1.21–3.70; P = 0.007). There were no deaths in the final cohorts. There were no worse outcomes in the Omicron COVID‐19 related croup group. Conclusions: The patients with COVID‐19 related croup exhibited more severe disease manifestations. These children were more likely to be admitted to the hospital/ICU and had more significant respiratory distress.